Catalytic Transfer of Fructose to 5-Hydroxymethylfurfural over Bimetal Oxide Catalysts - Qiuyun Zhang; Xiaofang Liu; Tingting Yang; Quanlin Pu; Caiyan Yue; Shuya Zhang; Yutao Zhang (International Journal of Chemical Engineering)
Direct conversion of fructose into 5-hydroxymethylfurfural (HMF) is achieved by using modified aluminum-molybdenum mixed oxide (S-AlMo) as solid acid catalysts. The synthesized catalyst was characterized by powder XRD, nitrogen adsorption-desorption isotherm, NH3-TPD, and SEM. As a result, the presence of strong acidity, mesostructures, and high surface area in the S-AlMo catalyst was confirmed by nitrogen adsorption-desorption isotherm and NH3-TPD studies. A study by optimizing the reaction conditions such as catalyst dosage, reaction temperature, and time has been performed. Under the optimal reaction conditions, HMF was obtained in a high yield of 49.8% by the dehydration of fructose. Moreover, the generality of the catalyst is also demonstrated by glucose and sucrose with moderate yields to HMF (24.9% from glucose; 27.6% from sucrose) again under mild conditions. After the reaction, the S-AlMo catalyst can be easily recovered and reused four times without significant loss of its catalytic activity.